Musculoskeletal Injuries Among Female Soldiers Working With Dogs. Issue 9 (18th May 2018) - Schermann, Haggai; Karakis, Isabella; Ankory, Ran; Kadar, Assaf; Yoffe, Victoria; Shlaifer, Amir; Yanovich, Ran
Abstract: Introduction: Female soldiers serving in the Israeli Defense Forces canine unit may be at increased risk of overuse injuries related to working with military dogs. We hypothesized that this particular type of occupational exposure may lead to an increased strain of the upper extremity due to such non-physiologic motions as pulling the dog's strap or resisting the sudden pulling by the dog, and may result in an increased rate of overuse injuries. Materials and Methods: We compared incidence of overuse injuries in a retrospective cohort of female soldiers who served either in the military working dogs' unit (MWD), or in the light infantry battalions (Infantry) from 2005 to 2015. We compared injury incidence of both groups during two periods: 5 mo of basic training (neither worked with dogs) and 19 or more months of combat service. Incidence was calculated as number of diagnoses per person-months (rate ratios, RR); each diagnosis counted once per study subject. We used RR confidence intervals to compare incidence of injuries between groups. Results: There were 3, 443 person-months in the MWD group and 194, 590 person-months in the Infantry group. There was no difference in injury incidence between groups during the initial period of basic training. During the second period, MWDs had higher incidence of upper limb (RR = 1.45, p = 0.048) and hip (RR = 3.6, p < 0.0001) injuries. The association between service with dogs and upper limb injuries remained significant (RR = 1.09, p = 0.005) after adjusting for confounding variables in the multivariate regression analysis. Other independent predictors of the upper limb overuse injuries included each additional month of service (RR = 1.003, p = 0.008), Eastern European origin compared with Israeli-born recruits (RR = 0.97, p = 0.03), increased body weight in increments of 10 kg (RR = 1.008, p = 0.03), anemia (RR = 1.02, p = 0.02) and fatigue (RR = 1.05, p ≤ 0.0001). Conclusions: We found that service in the MWD unit was associated with increased risk of upper limb injuries. Identification of the exact mechanism of injury and targeted interventions, as well as treatment of anemia and fatigue may lead to reduction of injuries in this unit.